Evaluation of clinical, biochemical and hematological parameters in macrocytic anemia - Thimmappa, Nalina; S. B., Vijeth; G., Prashanth; B. K., Sreedevi (International Journal of Advances in Medicine, 2019)
Background: Macrocytosis can be seen in many hematological and non-hematological disorders and more than one cause may co-exist in an individual. Serum vitamin B12 and folic acid tests are routinely ordered but they are limited by their low sensitivity and specificity. This study is done to analyze the clinical, hematological and biochemical parameters in macrocytic anemia and to study the difference between megaloblastic and non-megaloblastic anemia in these parameters. Methods: There were 100 patients presenting with macrocytosis were taken in to study. A detailed clinical history and physical examination was done in all cases. CBC, biochemical investigations, peripheral blood examination, Vitamin B12, folate levels, bone marrow aspiration and reticulocyte count was done in all cases. Results: Primary bone marrow disorders were the most common cause of macrocytosis (45%). The other causes in decreasing order of frequency were megaloblastic anemia (36%), alcoholism and liver disease (15%), drug induced (2%) and idiopathic thrombocytopenic purpura (1%). There was a significant difference in the mean values of MCV and serum LDH between megaloblastic and non-megaloblastic macrocytosis. When serum LDH >1124.5IU/L or MCV>120.5fl (criterion values of ROC curve) with reticulocyte count <2% was taken as criteria, the sensitivity was 94.4% and specificity was 93% for diagnosing megaloblastic anemia. Conclusions: Systematic evaluation of macrocytosis will help us to distinguish megaloblastic and non-megaloblastic macrocytosis. The blood and biochemical parameters especially CBC, RC, and serum LDH along with supporting clinical features help us in diagnosing megaloblastic anemia in a setup where vitamin and metabolite levels are difficult to obtain.